1973
DOI: 10.1037/h0034235
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic drive and altruistic reinforcement.

Abstract: People will learn an instrumental conditioned response, the reinforcement for which is the deliverance of another human being from suffering. Three experiments demonstrated this basic effect (p < .01 or better), as well as altruistic analogs of magnitude of reinforcement (p < .003) and intermittent shock (/><.001). The finding that people will not only help others who are in need, but find it rewarding to do so, indicates that altruism is even more deeply rooted in people than had been previously demonstrated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 44 publications
2
37
0
1
Order By: Relevance
“…Several theorists have argued that emergency situations produce arousal in the bystanders (Batson & Coke, 1983;Piliavin, Davidio, Gaertner, & Clark, 1981;Weiss, Boyer, Lombardo, & Stich, 1973). The rcsults of the present research contribute to these arguments.…”
Section: Discussionmentioning
confidence: 50%
“…Several theorists have argued that emergency situations produce arousal in the bystanders (Batson & Coke, 1983;Piliavin, Davidio, Gaertner, & Clark, 1981;Weiss, Boyer, Lombardo, & Stich, 1973). The rcsults of the present research contribute to these arguments.…”
Section: Discussionmentioning
confidence: 50%
“…Some have studied why it is that different people react quite differently to the same set of circumstances (Dabrowski, 1964;Hoffman, 1994;Weiss, Boyer, Lombardo, & Stich, 1973). Dabrowski was a Polish psychiatrist who witnessed the terrible effects of both World Wars.…”
Section: Background Of the Studymentioning
confidence: 98%
“…For example, two studies indicated that watching others who appeared to be receiving electric shocks followed by a warning signal could cause observers to form empathic reactions to the warning signal (Berger, 1962;DiLollo & Berger, 1965). The observers terminated the electric shocks more quickly when they believed they were able to help (Weiss, Boyer, Lombardo, & Stich, 1973). These studies suggest that the empathic response can be elicited by classical and operant conditioning.…”
Section: Social and Counseling Psychologymentioning
confidence: 99%